2009
DOI: 10.2190/pm.39.1.d
|View full text |Cite
|
Sign up to set email alerts
|

Repetition of Suicide-Related Behavior: A Study of the Characteristics, Psychopathology, Suicidality and Negative Life Events in Iran

Abstract: Some of the characteristics of patients with repeated suicide-related behavior propose major clinical challenges that should be addressed in an endeavor to reduce suicide risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In this study the following social factors were significantly associated with suicidal ideation and attempts: lack of social support, HIV stigma, being assaulted due to HIV and negative life events associated with children, and low perceived need for moral and practical social support. Previous studies among HIV-positive persons reported the following social factors to be associated with suicidal ideation and attempts: food insecurity; increasing number of negative life events and increasing stress scores [ 30 ]; physical and sexual abuse [ 43 ]; socioeconomic pressures and relational problems [ 13 ]; HIV stigma [ 54 59 ]; negative life events [ 30 , 60 62 ]. Kinyanda and colleagues [ 61 ] among a general hospital population which was not assessed for HIV status in urban Kampala reported the following additional social factors to be associated with attempted suicide: living in overcrowded tenements ( Mizigos ), negative life events in childhood, negative life events in later in life, and negative life events in the previous year [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study the following social factors were significantly associated with suicidal ideation and attempts: lack of social support, HIV stigma, being assaulted due to HIV and negative life events associated with children, and low perceived need for moral and practical social support. Previous studies among HIV-positive persons reported the following social factors to be associated with suicidal ideation and attempts: food insecurity; increasing number of negative life events and increasing stress scores [ 30 ]; physical and sexual abuse [ 43 ]; socioeconomic pressures and relational problems [ 13 ]; HIV stigma [ 54 59 ]; negative life events [ 30 , 60 62 ]. Kinyanda and colleagues [ 61 ] among a general hospital population which was not assessed for HIV status in urban Kampala reported the following additional social factors to be associated with attempted suicide: living in overcrowded tenements ( Mizigos ), negative life events in childhood, negative life events in later in life, and negative life events in the previous year [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variables associated with repeated attempts are poorly described. Previously, Sheikholeslami et al, 20 reported a higher risk of repeated attempted suicide among Iranian people who had psychiatric comorbidity and were receiving poor social support. Our study revealed a significant high risk of suicide repetition among women suffering from psychiatric disorders, which is in line with Sheikholeslami's report and confirms that psychiatric disorders are major determinants of repetition of attempted suicide.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that rumination was associated positively with both depression and anxiety; whereas brooding was related to co-morbid obsessive-compulsive disorder and generalized anxiety disorder, rumination was associated with traits associated with borderline personality disorder, most notably self-reports of unstable relationships and inconsistent sense of self, and associated with reports of sexual abuse. Post (2010) recounts that over and above the genetic vulnerability endowed by an array of epigenetic factors (Mendlewicz 2009), the liability for disease progress of recurrent affective disorders may be due to environmental factors, such as (i) distal and proximal stressors, (ii) the recurrence of the episodes themselves, and (iii) comorbidity with abuse of drugs, e.g., cocaine (but see also LeBlanc et al 2009;Sheikholeslami et al 2009;Simpson et al 2009). It is described that each may develop sensitization and/or cross-sensitization to each of the other factors, thereby 'driving' disease progression as observed under clinical conditions through cyclical acceleration, episodic severity/duration, disability on neurocognitive tasks, general disability, and premature death.…”
Section: Staging In Affective Disordersmentioning
confidence: 99%